KOMUNIKASI ANTARPRIBADI MAHASISWA DI PONDOKAN X RT1/RW3 KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Haniza, Sopi Haniza; Maemunaty, Titi Maemunaty; Achmad, Said Suhil Achmad Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT :Based on the result observation on 7 June 2014 at Pondokan X RT1/RW3 the village Simpang Baru subdistrict Tampan city of Pekanbaru, there are: (1) some occupants unfriendly, (2) founded some of groups among occupants. The aim of this research is to know the interpersonal communication colleger at Pondokan X RT1/RW3 the village Simpang Baru subdistrict Tampan city of Pekanbaru, kind of the communication are: (i) communication among two persons or more, (ii) informal situation, (ii) kind of focuse interaction, (iv) exchange of verbal and non verbal signal, (v) feed back. The focuse of this research are include of some aspects, there are place, actor, and the activity that was done by the occupants of Pondokan X RT1/RW3 the village Simpang Baru subdistrict Tampan city of Pekanbaru. This research used qualitative from fenomenology, fenomenology is let something become real as look live a real. The research get an information from the owner, of Pondokan X as key informant, and the visitor as control informant. The research get the data by using observation method, interview, and documentation. Accumulation and analysis the are: (1) domain analysis, (2) taksonomy analysis, (3) componential analysis, (4) culture analysis. Keyword: communication, communication interpersonal, and college